Role of Facebook Advertising in Promoting Tourism in Asia - Rezeki Ananda Lubis, Fajar; Suharyanto, Agung; Effendy, Rochmat; Eka Meidasari, Venny; Shahnaz, Liza (International Journal of Psychosocial Rehabilitation, 2020)
Let us inspect Asian growth on Facebook. We tend to bring you latest growth of states within the last six months. Asia has over 166 million folks victimization Facebook these days thus let's take a better look on the expansion of the highest ten countries within the last six month. With the rise of eleven.3 million users is Republic of India the quantity one growing country on Facebook in Asia. At the start of year 2011, Republic of India had Facebook population of seventeen.3 million users and through the six-month amount the quantity of users will increase to twenty-eight.6 million. The large increase corresponds to sixty-five percentage change. India is follow by land that has six million new users. The third place belongs to Philippines with the rise of million users. The fourth place belongs to Asian country. Top list of most growing countries in Asia is closed by Japan. Japan really doubled the quantity of Facebook users throughout the last six months. At the start of year, 2011 Japan had just one.8 million Facebook users wherever currently range of users has passed three.7 million! This corresponds to modification that is that the highest growth within the Asian countries overall.